Increasing Family Revenue Based on Household Industry - Arianty, Nel (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Nowadays, domestic business actors should be able to prepare themselves and have a good strategy in producing quality products and have a wide marketing network, so that the market or consumer can accept the products, so that small industry business can increase family income.